Pengaruh Media Sosial Akun Instagram @pandawaragroup Terhadap Perilaku Kepedulian Lingkungan - Muhammad Agung Dwi Tjandra; Prahesti, Riska Tyas (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Social media represents a significant advancement in information technology that plays an essential role in facilitating communication and social interaction within society. Environmental care behavior reflects individual efforts to support and promote environmental sustainability. This study specifically targets Generation Z and millennials as future generations, emphasizing the importance of instilling environmental awareness and encouraging the maintenance of environmental cleanliness in all settings. Based on these considerations, the Instagram account @pandawaragroup was selected as the independent variable of this study, with a primary focus on environmental care behavior influenced by the content shared on the account. This research aims to examine the extent to which the Instagram account @pandawaragroup affects environmental care behavior. A quantitative research approach was employed, utilizing a random sampling technique by distributing questionnaires to 100 respondents who are followers of the @pandawaragroup Instagram account. Data analysis was conducted using simple linear regression with the assistance of IBM SPSS version 2025. The results of the hypothesis testing indicate that the use of the Instagram account @pandawaragroup has a significant effect on environmental care behavior, with a coefficient of determination of 17%. This finding suggests that the Instagram account @pandawaragroup contributes 17% to shaping environmental care behavior, while the remaining 83% is influenced by other factors beyond the scope of this study.